MHD hyperbolic tangent Casson-Williamson nanofluid over a linearly stretching sheet with thermophoresis and Brownian motion - Reddy, Shashidar Borra; Reddy, B. Narsimha; Saritha, Kallu; Chesneau, Ch. (Zielona Góra: Uniwersytet Zielonogórski)
The main aim of this research is to investigate the effects of Brownian motion and thermophoresis on an MHD hyperbolic tangent Williamson-Casson nanofluid passing over a stretching sheet. Through appropriate similarity transformations, non-linear partial differential equations governing the model can give rise to non-linear ordinary differential equations. These equations are solved numerically using the Keller-Box method.
Keywords: Casson fluid; Williamson fluid; Brownian motion; thermophoresis; suction; Keller-Box method; Hartmann number; Prandtl number